Terrorism and inbound tourism in Egypt: Economy-wide and distributional impacts - Elshennawy, Abeer; Siddig, Khalid (Wiley, 2023)
Following the January 2011 Revolution, Egypt experienced increasing political instability and has also been the target of intense terrorist attacks. While substantial efforts continue to be exerted by the current regime to put an end to these attacks, it is not clear whether the country's reputation as a safe tourist destination will be restored in the medium run. This paper assesses the extent of the Egyptian economy's vulnerability to a prolonged tourism shock using an economy‐wide framework. The simulation results reveal that a shock to tourism has a significant impact on the Egyptian economy, as a rebound of inbound tourism substantially increases both GDP and welfare. Consequently, it pays for the government to put measures in place to moderate the effect of negative shocks to inbound tourism. A subsidy to health tourism was found to boost both economic growth and welfare.